Craniofacial and other typical deficits in children with Foetal Alcohol Syndrome - FAS in the context of Foetal Alcohol Spectrum Disorders - Barbora Vodičková; Petra Mitašíková (Listy klinicke logopedie, 2023)
The article describes the impact of prenatal alcohol exposure (PAE) in the context of the development of craniofacial and other typical deficits in children with foetal alcohol syndrome - FAS. FAS is the most serious diagnosis of foetal alcohol spectrum disorders - FASD. FASD is a non-diagnostic umbrella term for possible consequences of PAE. It is a set of anatomical malformations and neurodevelopmental abnormalities created during intrauterine development of an individual due to alcohol consumption by the mother during pregnancy. There are several diagnostic manuals worldwide for the diagnosis of FASD, including FAS. The 4-Digit Code according to Astley (2004) is currently used in Slovakia. The given manual has a very well-researched section on the diagnosis of craniofacial deficits. In FAS, the typical signs on the face are what are called the sentinel facial features. These include a short palpebral fissure, a narrow upper lip, and a smooth crease between the nose and the upper lip. From the point of view of Speech Therapy, it is also important to know about anomalies in the development of the teeth, lips, palate, nose, ears and eyes. As part of the aetiology of craniofacial and other typical deficits, molecular, biochemical, cellular and embryonic mechanisms are generally mentioned.